European Policy for Protection of Whistle-Blowers Who Report Irregularities, Fraud and Corruption and the Bulgarian Reality - Yosifova, Milka (Research Papers, 2019)
According to Art. 45 of the Constitution of the Republic of Bulgaria (CRB), citizens have the right to complaints, proposals and petitions to the state authorities. It is a means of civil control over the activities of state authorities and the opportunity for the administration to improve and democratize its activities. The aim is to remedy the violations, irregularities and harmful effects of illegal and inappropriate actions of the state administration, the government and the parliament. The problems and different practices in the EU Member States highlight the debate on a common policy based on research, good and effective practices and achievements. The task is to achieve a legal order and security for every citizen and to assure his rights, powers and duties to cooperate and fight against everything that violates the democratic principles and values, economic prosperity and the rule of law. Bulgarian legislation, including the Constitution, does not provide sufficient protection for whistleblowers. In the study, with the mechanisms of a comprehensive analysis in 10 consistently binding points of view, the problem was explored in order to draw attention to the need for a pan-european directive that would regulate EU relationships in the name and the value of democracy.
Keywords: Signals; Irregularities; Citizens; Protection; Corruption; Еmployees